Effect of heat stable carbetocin vs oxytocin for preventing postpartum haemorrhage on post delivery hemoglobin–a randomized controlled trial. (12th December 2022) - Vernekar, Sunil S.; Goudar, Swati S.; Metgud, Mrityunjay; Pujar, Yeshita V.; Somannavar, Manjunath S.; Piaggio, Gilda; Carvalho, José Ferreira D. E.; Revankar, Amit; Althabe, Fernando; Widmer, Mariana; Gulmezoglu, Ahmet Metin; Goudar, Shivaprasad S.
Abstract: Objective: To compare the effect of heat-stable carbetocin 100 μg IM versus oxytocin 10 IU IM on post-delivery hemoglobin level. Setting: Hospital based study in Southern India. Population: Women delivering vaginally who were enrolled in the WHO CHAMPION trial in a single facility in India. WHO CHAMPION Trial was a randomized, double-blind, noninferiority trial comparing intramuscular injections of heat-stable carbetocin with oxytocin administered immediately after vaginal birth in women across 23 sites in 10 countries. Methods: This was a nested randomized controlled trial designed to compare the effect of heat-stable carbetocin 100 μg IM versus oxytocin 10 IU IM, administered within one minute of vaginal delivery of the baby for prevention of postpartum hemorrhage, on post-delivery 48–72 h hemoglobin level, adjusted for pre-delivery hemoglobin level. 1, 799 women from one hospital in India participated in this study. Results: Pre-delivery hemoglobin and postpartum blood loss were not significantly different between carbetocin and oxytocin. Post-delivery hemoglobin, unadjusted or adjusted for pre-delivery hemoglobin, was slightly lower for carbetocin (10.09 g/dL) compared to oxytocin (10.21) (p value of 0.0432). The drop in hemoglobin was slightly higher for carbetocin, although the difference was very small (1.2 g/dL for carbetocin, 1.1 g/dL for oxytocin) ( p value of .0786). The proportion of participants with a drop in hemoglobin of 2 g/dL or more, adjusted for pre-delivery hemoglobin, was higher for carbetocin (RR = 1.29, 95% CI 1.02–1.63). From the regression coefficients it can be derived that post-delivery hemoglobin, adjusted for pre-delivery hemoglobin, decreases on average 0.12 g/dL for each dL of blood lost, for the two treatments combined. Conclusion: The present ancillary study showed that intramuscular administration of 100 µg of heat stable carbetocin can result in a slightly lower post-delivery hemoglobin, slightly higher drop and higher percentage of women having a drop of 2 g/dL or larger, compared to 10 IU of oxytocin.